Cover Vol 12, No 2 (2020) - Jurnal Al Amwal (UIN Siber Syekh Nurjati Cirebon, 2020)
Al-Amwal: Jurnal Ekonomi dan Perbankan Syariah is journal published by the Department of Islamic Banking Syariah Faculty of Islamic Economics of IAIN Syekh Nurjati Cirebon. The journal publishes papers in the field of accounting and finance that give significant contribution to the development of economic and sharia banking profession in Indonesia. The journal published twice a year. The journal has been accredited SINTA 3 at 4th April 2019 by Indonesia Ministry of Research, Technology and Higher Education (RistekDikti) of The Republic of Indonesia as an academic journal in Director Decree (SK Dirjen No. 10/E/KPT/2019)